-21-6x=27-8x

Simple and best practice solution for -21-6x=27-8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -21-6x=27-8x equation:



-21-6x=27-8x
We move all terms to the left:
-21-6x-(27-8x)=0
We add all the numbers together, and all the variables
-6x-(-8x+27)-21=0
We get rid of parentheses
-6x+8x-27-21=0
We add all the numbers together, and all the variables
2x-48=0
We move all terms containing x to the left, all other terms to the right
2x=48
x=48/2
x=24

See similar equations:

| 6r+3=2r+11= | | 7(f-85)=77 | | 8a+a-3=4a-3 | | 9(v-91)=27 | | 19y-11=-11+12y | | -7(-2x-8)=24 | | 10x-6+1=5x | | 8(8)+x=15(15) | | 157.74=6(0.06m+19.70+0.10(19.70) | | 5p+6=(-14) | | 1/3(6x-12)=-14 | | 5x+8-7x=13-13x+11x-5 | | 2x(3x-2)=4 | | -3(v-5)+5v=2(v-6) | | 8m=4m-16 | | 3(3z+2)-7=62 | | 5-2{x+5}=30 | | x/2-8=-16 | | 2x-(-x+4)=x+(-2) | | -32=20-4n | | 7x=106-10(5) | | -105=-792x=30 | | Y-5=3y-5 | | -20-x=-64 | | 5x(x+4)=7+(x-2) | | 1+16t-13=16t+16 | | (2x+3)+(5x-13)+(3x)=180 | | 2/5(3x+1)=16 | | 18+f=-2f-19+10 | | x2+9=46 | | -3.75*m=5.5 | | 31=6x=7 |

Equations solver categories